Tracking Live‐Cell Response to Hexavalent Chromium Toxicity by using Scanning Electrochemical Microscopy. Issue 4 (16th February 2017) - Henderson, Jeffrey D.; Filice, Fraser P.; Li, Michelle S. M.; Ding, Zhifeng
Abstract: The effects of exposure to toxic heavy metals, such as chromium, are of interest in scientific research, owing to its association with oxidative stress, cytotoxicity, and carcinogenicity. This study aims to explore the effects of Cr (VI) on live cell responses. Herein, scanning electrochemical microscopy (SECM) is employed by using depth scan imaging and feedback mode to monitor the membrane permeability of single live human bladder cancer (T24) cells following 1 h incubations with Cr (VI) stimuli. By using membrane‐permeable and impermeable redox mediators, ferrocenemethanol and ferrocenecarboxylic acid, respectively, SECM depth scans yield both electrochemical and topographic information. This provides insights into the relative changes in membrane homeostasis with increased exposure to Cr (VI). Here, SECM has shown great power in determining membrane response to Cr (VI) exposure. Dependent on the level of exposure, transition between three distinct trends was observed. At low incubation concentrations of Cr (VI), the cell membrane permeability coefficients were relatively unaffected. With moderate increases in Cr (VI) concentrations, membrane permeability coefficients of the incubated cells were observed to decrease. Finally, with the higher incubation concentrations, membrane permeability coefficients were found to increase toward values similar to control cells. The Cr (VI) toxicity was further investigated by means of a MTT cell viability study, which exhibited a similar decreasing trend to the cell membrane permeability. These findings further demonstrate the strength of SECM as a bioanalytical technique for monitoring cellular homeostasis. Abstract : Cr (VI) driven permeability change : This study explores the effects of Cr (VI) on live‐cell response. Human bladder cancer (T24) cells are incubated with varying concentrations of Cr(VI) and cell membrane permeability is monitored by using membrane‐permeable and ‐impermeable redox mediators, ferrocenemethanol and ferrocenecarboxylic acid, respectively (see picture). Change in membrane permeability correlates with changes in cell viability.